Design and implementation of an intelligent monitoring system for real-time tip-over assessment of mobile manipulator - Lupoy, Mark Lawrence D. (Animo Repository, 2023)
Mobile manipulators are commonly used for explosive ordnance disposal (EOD) missions. The typical operation of an EOD robot includes traversing inclines as well as a variety of rough terrains while carrying heavy payloads which may cause postural instabilities or tip-over. Mobile manipulator tip-over, especially while carrying payload, creates a dangerous situation for the surrounding environment resulting in an aborted mission. This study aims to create a real-time tip-over monitoring system that can be applied to avoid a mobile manipulator tip-over. Using a Computer Aided Design (CAD) model of the robot and parameters such as center of gravity and orientation, a measure for robot instability and a tip-over algorithm can be derived and evaluated to perform the necessary actions such as adjusting robot arm positions or changing velocity of the robot to prevent tip-over.